Serological and genetic characterisation of a unique strain of adenovirus involved in an outbreak of epidemic keratoconjunctivitis. Issue 4 (26th March 2004) - Adhikary, A K; Inada, T; Banik, U; Mukouyama, A; Ikeda, Y; Noda, M; Ogino, T; Suzuki, E; Kaburaki, T; Numaga, J; Okabe, N
Abstract : Aims: To characterise a novel strain of adenovirus (Ad) type Ad8 (genome type Ad8I) involved in an epidemic keratoconjunctivitis (EKC) outbreak in Hiroshima city using serological testing and sequence analysis of the fibre and hexon gene. Methods: A neutralisation test (NT) was performed in microtitre plates containing a confluent monolayer of A549 cells using 100 tissue culture infectious doses of virus and type specific antisera. The haemagglutination inhibition test was also carried out in microtitre plates with rat erythrocytes using four haemagglutination units of virus and twofold dilutions of serum. The fibre gene was sequenced by generating overlapping polymerase chain reaction products or by direct sequencing of genomic DNA. Primer selection was based on alignment of the fibre genes of human adenovirus serotypes Ad8, Ad19, Ad37, Ad9, and Ad15 available from Gene Bank. Results: The virus strain was specifically neutralised by anti-Ad8 antibodies, although there was a major crossreaction with anti-Ad9 antibodies. Haemagglutination was equally inhibited by anti-Ad8 and anti-Ad9 antibodies. The predicted amino acid sequences of the hypervariable regions (HVRs) of the Ad8I hexon gene showed higher homology with Ad9 (83.3%) than with Ad8 (62.0%). However, the Ad8I fibre knob was more homologous to Ad8 (94.4%) than to Ad9 (91.6%). Conclusions: Ad8I is a unique strain of adenovirus because of its lower genomic homology with Ad8, major crossreactivity with Ad9 in NT, and mixed genetic organisation of HVRs of the hexon gene. These factors may have enabled the virus to circumvent acquired immunity, resulting in the outbreak.